Estudio de prefactibilidad para la instalación de una planta procesadora de hot dogs con fibra dietética de cáscara de plátano - Mauricio Gonzáles, Carolina Antonella (2019)
This project consists in a pre-feasibility study regarding the implementation of a hot dog manufacturing plant, which includes dietary fiber in its composition extracted from banana peel. In this study the technical, economic and market viability were assessed. This project has as target market citizens from Lima Metropolitana who belong to A and B socioeconomic levels. With the development of this market study, the project demand was estimated from 2018 to 2024. The study shows that the hot dog market has a great growth potential, due to the great gap between the potential demand of 159,207,713 kg estimated for year 2017 and the domestic demand of 31,308,370 kg for the same year. In order to determine the ideal location of the plant, macro and micro localization studies were performed, resulting in the department of Lima, province of Cañete and district of Chilca as the most profitable choice. Later, the market was established as a restricting production factor with a maximum demand in the year 2024 of 280,822 hot dog kilograms. Regarding the engineering of this project, the technology and machinery required for each stage of the production process were detailed throughout the study. In addition, for the plant allocation, the necessary layouts were established, and the areas calculated, obtaining the final size of 744 m2. On the other hand, in the economic and financial aspects, the investment required was S/. 1,491,589, financed 60% by own capital and 40% through a bank loan. By determining the economic and financial flow, it was obtained an economic NPV of 962,306 and a financial NPV of S/. 1,188,479. This indicates significant returns over the project period. Finally, towards the social evaluation it was estimated an indicator Capital/Product of 4.46, which shows that this project will generate 4.46 times value added per sol invested. So, it can be concluded that the project will have a positive impact on economic growth of the influenced areas.